The Research Progress on the Effects of Phytohormones on Nitrogen Use Efficiency in Rice - Kunlun Liu; Xingyi Liang; Weiling Wang; Zhongyang Huo; Can Zhao (Plants, 2025)
Nitrogen (N) is one of the most important nutrients determining crop growth performance. With the increasing demand for sustainability in global agriculture, improving nitrogen use efficiency in rice has become a critical issue. Nitrogen use efficiency (NUE) in rice is a complex trait influenced by multiple factors, among which phytohormones play a key role. NUE is primarily regulated through the influence of phytohormones on absorption, transport, assimilation, and utilization processes. In this review, we focus on these interactions and summarize the relationships between major hormones and nitrogen use efficiency in rice. Finally, we outline the current challenges and future research prospects in this field. Although studies have shown promising results for their role in improving crop NUE, the specific mechanisms remain unclear. Additionally, the interactions among phytohormones and the influence of environmental factors on their effectiveness require further investigation. This review provides theoretical support and technical guidance for understanding the role of phytohormones in rice NUE and offers insights into improving NUE in rice.